Security Efficiency Maximization for Multi-UAV–Aided Network With Mobile Edge Computing - Mu, Guangchen (Frontiers in Computer Science, 2021)
In this paper, we consider a security efficiency maximization problem in a multiple unmanned aerial vehicles (UAVs) aided system with mobile edge computing (MEC). Two kinds of UAVs, including multiple computing UAVs (CUAVs) and multiple jamming UAVs (JUAVs), are both considered in this system. CUAVs would receive partial computation bits and send the computation results to ground users. JUAVs do not undertake computing tasks, and only sends interference signals to counter potential ground eavesdroppers. We jointly optimize the ground users scheduling, UAVs power and UAVs trajectory to maximize the security efficiency. The original problem is non-convex and difficult to solve. We first use Dinkelbach combined with continuous convex approximation technology, and then propose three corresponding sub-problems, including user scheduling sub-problem, UAVs power sub-problem and UAVs trajectory problem. Further, we apply the branch and bound method to solve the user scheduling sub-problem, and optimize the two remaining sub-problems by introducing auxiliary variables and Taylor expansion. The simulation results show that the proposed scheme can obtain better secure offloading efficiency with respect to the existing schemes.